Florescano, E., y Sánchez Díaz. G. (2018). El pescado blanco. En la historia, la ciencia y la cultura michoacana. Universidad Michoacana de San Nicolás de Hidalgo. 341 pp. - Quiroz Muñoz, Enriqueta (Letras Históricas E-ISSN: 2448-8372, 2020)
Reseña de libro.